2020
DOI: 10.20411/pai.v5i1.370
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunity to <em>Vibrio cholerae</em> O1 Afforded by a Human Monoclonal IgA1 Antibody Expressed in Milk

Abstract: Background: In cholera epidemics, the spread of disease can easily outpace vaccine control measures. The advent of technologies enabling the expression of recombinant proteins, including antibodies, in the milk of transgenic animals raises the prospect of developing a self-administered and cost-effective monoclonal antibody (MAb)-based prophylactic to reduce the incidence of Vibrio cholerae infection.Methods: We generated a transgenic mouse line in which the heavy and light chain variable regions (Fv) specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“… 29 31 While there are examples in which passively administered mouse IgA or SIgA has been shown to afford immunity against experimental shigellosis and cholera, the use of human SIgA is only beginning to be explored. 32 35 For example, we recently showed in a mouse model of invasive Salmonella infection that Sal4 IgA, an anti-lipopolysaccharide mouse mAb, was sufficient at reducing the invasion of Salmonella enterica serovar Typhimurium (STm) into Peyer’s patch tissues. 36 Sal4 SIgA was superior to Sal4 IgG.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 29 31 While there are examples in which passively administered mouse IgA or SIgA has been shown to afford immunity against experimental shigellosis and cholera, the use of human SIgA is only beginning to be explored. 32 35 For example, we recently showed in a mouse model of invasive Salmonella infection that Sal4 IgA, an anti-lipopolysaccharide mouse mAb, was sufficient at reducing the invasion of Salmonella enterica serovar Typhimurium (STm) into Peyer’s patch tissues. 36 Sal4 SIgA was superior to Sal4 IgG.…”
mentioning
confidence: 99%
“…These unique attributes have garnered interest in SIgA as an alternative or supplement to antibiotic-based therapeutics for enteric diseases. Recent advancements in the generation of recombinant antibodies via multivector mammalian expression systems have enabled the production of SIgA monoclonal antibodies (mAbs). While there are examples in which passively administered mouse IgA or SIgA has been shown to afford immunity against experimental shigellosis and cholera, the use of human SIgA is only beginning to be explored. For example, we recently showed in a mouse model of invasive Salmonella infection that Sal4 IgA, an anti-lipopolysaccharide mouse mAb, was sufficient at reducing the invasion of Salmonella enterica serovar Typhimurium (STm) into Peyer’s patch tissues . Sal4 SIgA was superior to Sal4 IgG .…”
mentioning
confidence: 99%
“…During the course of infection, class-switching to IgA and the secretion of antigen-specific secretory IgA (S-IgA) serves as the main means of protection by binding to V. cholerae and preventing pathogen access to epithelium, and neutralizing cholera toxin ( Apter et al., 1993 ). Recent studies have also indicated that anti-O-specific polysaccharide antibodies in sera from humans surviving cholera can agglutinate Vibrio and prevent motility ( Charles et al., 2020 ), and that expression of a monoclonal human anti-LPS IgA1 in mice can provide passive protection to infants from milk ( Baranova et al., 2020 ). For an up-to-date article of cholera immunity, please read Holmgren J, Trop.…”
Section: Resultsmentioning
confidence: 99%
“…76 Alternative strategies such as transgenic animals that express human MAbs including human IgA in colostrum and breast milk are also worthy of investigation, especially considering their track record with other biologics. 77,78 While oral administration of MAbs and MAb cocktails has obvious benefits over intravenous and subcutaneous routes of delivery, the pharmacokinetics and stability of SIgA in the human gastric and intestinal environments remain unknown and need to be taken in consideration. 55,57 Within the context of the gut, the benefit of SIgA over IgG is obvious and is likely due to SIgA glycosylation and resistance to intestinal proteases.…”
Section: Summary and Perspectivesmentioning
confidence: 99%